The complete mitochondrial genome of Schizopygopsis chengi baoxingensis (Teleostei, Cyprinidae, Schizopygopsis). (3rd May 2016) - Li, Hua; Huang, Yong; Li, Qiang; Chen, Yeyu; Liu, Ya; Liu, Guangxun
Abstract: Schizopygopsis chengi baoxingensis is endemic to the Baoxing River in China and may become an endangered species due to its very narrow habitat and the construction of hydropower dams. In this study, we successfully sequenced the first mitochondrial genome of S. c. baoxingensis . The mitogenome is 16, 787 bp in length, containing 13 protein-coding genes, two rRNA genes, 22 tRNA genes and a control region (D-loop). The overall base composition of the H-strand is 28.5% A, 26.2% T, 18.4% C, and 26.9% G, with a slight AT bias of 54.7%. The sequenced mtDNA genome of S. c. baoxingensis is similar in gene arrangement to that of other cyprinidaes except for a 191 bp non-coding region found between tRNA Thr and tRNA Pro .